Pimping up Drugs Recovered, Superannuated and Under Exploited Drugs - An Introduction to the Basics of Drug Reprofiling - J. Dilly, Suzanne; S. Morris, George (Current Drug Discovery Technologies, 2017)
Drug development has moved along way forward from the days of with doctors peddling cauldrons of herbs and spices, however, the process can still miss opportunities for full exploitation of a drug’s potential. Drug reprofiling provides a chance for an established or a forgotten drug to move into a new area of therapy, whether related to the known effects or in a completely new area. In an era of environmental awareness and spiraling costs for traditional drug development, a strategy to squeeze every benefit out of drugs with known safety, tolerability and pharmacological parameters must be a strategically sound desire. We explore examples of success in reprofiling, draw comparisons between techniques, and finally provide two examples from the Valirx plc development pipeline currently undergoing the process.
Keywords: health economics